Digital Community Synergy: Integrating Parents and Teachers to Build Children's Character and Language Skills - Bawamenewi, Arozatulo; Telaumbanua, Arisman; Riana, Riana (Newinera Publisher, 2026)
This study examines a community-based digital education synergy model that integrates parents, teachers, and community support to strengthen children’s character and language skills in Gunungsitoli City. Focusing on listening, speaking, reading, and writing, the research employed a mixed-methods design with a dominant qualitative descriptive approach. Data were collected through observation, in-depth interviews, questionnaires, documentation, and a short micro-intervention involving technology-assisted language tasks. Participants included teachers, parents, students, and community informants from two elementary schools in rural settings with limited internet access, device availability, and varying levels of digital literacy. The findings show that children’s language development in the digital era is influenced not merely by technology use, but by the quality, consistency, and direction of adult guidance. Descriptive results indicate strong performance in gadget supervision (mean 3.58), literacy support (mean 3.57), and content mentoring and communication (mean 3.44), while parent-school collaboration showed the lowest score (mean 3.26), indicating the need for stronger two-way communication. The study formulates the 3P Cycle model Planning, Mentoring, and Assessment supported by four pillars: home-school communication, content curation and gadget governance, meaningful language practice, and community support. Girls tended to show stronger verbal expression and interpersonal communication, suggesting the importance of gender-sensitive mentoring strategies. The study concludes that technology becomes educationally effective when used wisely, consistently, and collaboratively. Strengthening home-school-community partnerships can foster children’s language competence, prosocial behavior, digital ethics, and safer learning ecosystems in the digital era. Practical recommendations include digital parenting training, reflective feedback journals, and community literacy spaces for sustained support.